2016
DOI: 10.1016/j.margeo.2016.10.016
|View full text |Cite
|
Sign up to set email alerts
|

Wave breaking patterns control rip current flow regimes and surfzone retention

Abstract: Abstract:Recent research into rip currents has revealed the existence of multiple circulation patterns, meaning that no single escape strategy is appropriate in all situations. Rip circulation is influenced by surfzone morphology, which can be inferred from wave breaking patterns in video imagery. Wave breaking often occurs over the bars adjacent to the rip channel, with little breaking over the seaward end of the rip. However, under varying wave and tide conditions, breaking can also occur at the seaward exte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 56 publications
2
21
0
Order By: Relevance
“…In addition to morphodynamic-zone studies, the technique can support the use of existing stand-alone automated procedures for coastal image analysis. Specific areas of the image can be previously extracted and/or masked to fasten, for instance, wave breaking height [25,45,46], rip currents [47][48][49][50], shoreline detection [35,[51][52][53][54], wave runup measurements [30,35,[55][56][57][58][59][60][61][62], and intertidal beach topography [28,29,36,61,[63][64][65][66]. The use of the technique can also be coupled to the existing algorithm that focus on beach morphological features detection [67][68][69][70][71] for a fully description of coastal area from coastal imaging.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to morphodynamic-zone studies, the technique can support the use of existing stand-alone automated procedures for coastal image analysis. Specific areas of the image can be previously extracted and/or masked to fasten, for instance, wave breaking height [25,45,46], rip currents [47][48][49][50], shoreline detection [35,[51][52][53][54], wave runup measurements [30,35,[55][56][57][58][59][60][61][62], and intertidal beach topography [28,29,36,61,[63][64][65][66]. The use of the technique can also be coupled to the existing algorithm that focus on beach morphological features detection [67][68][69][70][71] for a fully description of coastal area from coastal imaging.…”
Section: Discussionmentioning
confidence: 99%
“…As submerged sand bars cause preferential breakings over the bar crest, Timex images can be used to find the position and the long-shore development of submerged nearshore sand bars. This property has been exploited for the study of nearshore sand bar migration (e.g., [17][18][19]), rip currents (e.g., [20][21][22][23]), and beach state characteristics (e.g., [24][25][26][27][28]). Since on Timex the swash movements on the foreshore slope are smoothed out, several algorithms have been proposed for shoreline detection on Timex images (e.g., [4,[29][30][31]) and have been widely used for a long-term monitoring of shoreline change (e.g., [32][33][34]).…”
Section: Coastal Video Monitoring Applicationsmentioning
confidence: 99%
“…The lifeguards will see this and know to come and get you, and you might even attract the attention of other swimmers or surfers in the area who can help you out. Some research has shown that, often, rip currents will eventually bring you back toward the shore [4], so just keep floating and save your energy.…”
Section: What To Do If You Are Caught In a Rip Current!mentioning
confidence: 99%